THE EFFECTIVENESS OF MOZART CLASICAL MUSIC ON ANXIETY IN LABORING MOTHERS DURING LATEN PHASE AT TOROH IPRIMARY HEALTH CARE - Indah Sari; Rosmala Kurnia Dewi; Yuwanti (Lppm Unan, 2026)
Background; childbirth is natural physiological process, but it is often accompanied by intense emotional changes in mother, such as fear and anxiety. This anxiety can negatively impact the childbirth process, trigger a risk prolongation on the first and second stage, and increase the risk of complications such as infections and excessive pain. Psychologically anxiety can also hinder communication and social relationship, as well as affect the mother well-being. This study aims to analyze the effect of Mozart classical music therapy on the anxiety levels of mothers in the first stage of labor. Method; the research method used is quasi experimental, which is method involving the administration of treatment to determine the effect of the treatment on the research subject. Result; the hypothesis test using the Wilcoxon comparative test obtained results with a p-value 0f (0,001) < 0,05 meaning there is an effect of Mozart classical music therapy. Conclusion; there is an effect of classical music therapy on the anxiety level of mothers in the first stage of labor during the latent phase at Toroh I Community health center.